1999
DOI: 10.1074/jbc.274.27.18942
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated pbp4 in Highly Glycopeptide-resistant Laboratory Mutants of Staphylococcus aureus

Abstract: Microb. Drug Resist. 4, 159 -168). We now report that the distorted peptidoglycan composition is related to defects in penicillin-binding protein 4 (PBP4); no PBP4 was detectable by the fluorographic assay in membrane preparations from the mutants, and comparison of the sequence of pbp4 amplified from the mutants indicated disruption of the gene by two types of abnormalities, a 17-amino acid long duplication starting at position 305 of the pbp4 gene was detected in the vancomycin-resistant mutant, and a stop c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
1
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 25 publications
10
112
1
1
Order By: Relevance
“…Briefly, mutanolysin-digested peptidoglycan was separated by reversed-phase high pressure liquid chromatography for muropeptide analysis. Glycan chain analysis was performed according to the method for muropeptide analysis except that the cell wall was digested with lysostaphin instead of mutanolysin as previously described (20). For control purposes, some samples were also doubly digested with both enzymes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, mutanolysin-digested peptidoglycan was separated by reversed-phase high pressure liquid chromatography for muropeptide analysis. Glycan chain analysis was performed according to the method for muropeptide analysis except that the cell wall was digested with lysostaphin instead of mutanolysin as previously described (20). For control purposes, some samples were also doubly digested with both enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…To further characterize the cell surface structure of the atl null mutant, we prepared peptidoglycan from the wild type RN4220 and the mutant JT1392, and the enzymatic hydrolysates obtained by digestion with either mutanolysin (to analyze muropeptide composition) or lysostaphin (to detect possible alterations in sugar chain length distribution) were analyzed by high pressure liquid chromatography (20,21). Double digestions with both enzymes were analyzed as a control for completeness of enzymatic degradation.…”
Section: Cell Wallmentioning
confidence: 99%
“…In the late 1990s, Sieradzki et al suggested that alterations in cell wall structure inhibit vancomycin access to its active site in a laboratory-induced strain with a vancomycin MIC of 100 g per ml (315,320). Over recent years, a model of the resistance mechanism of hVISA and VISA has evolved, where VISA emerges by sequential mutations from VSSA, with hVISA as an intermediary between VSSA and VISA.…”
Section: Phenotypic Features and Mechanisms Of Resistancementioning
confidence: 99%
“…These studies have led to a model of vancomycin resistance in which decreased cell wall turnover and autolysis result in increased cell wall thickness and resistance to vancomycin. Mechanistically, the thickened cell wall is thought to limit the access of vancomycin to its target (6,9,11,12,26). Because this model of vancomycin resistance relies on an alteration in cell wall thickness, most research has focused on adaptations affecting cell wall thickening.…”
mentioning
confidence: 99%